2022
DOI: 10.1016/j.ijrobp.2022.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Variable Effect of the COVID-19 Pandemic on Radiation Oncology Practices in the United States

Abstract: Early in the pandemic, the American Society for Radiation Oncology (ASTRO) surveyed physician leaders at U.S. radiation oncology practices to understand how the field was responding to the outbreak of COVID-19. Surveys were repeated at multiple points during the pandemic, with a response rate of 43% in April 2020 and 23% in January 2021. To our knowledge, this is the only longitudinal COVID-19 practice survey in oncology in the U.S. The surveys indicate that patient access to essential radiation oncology servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Furthermore, the American Society for Radiation Oncology (ASTRO) recently performed a longitudinal survey, which indicated that patient access to radiotherapy was preserved during the pandemic, and most institutions did not defer or postpone the treatment in early 2021. In addition, telemedicine was commonly used in metropolitan areas [ 9 ]. In Japan, some institutions experienced a decrease in the number of patients receiving radiotherapy, and the number of patients was limited in the early stages of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the American Society for Radiation Oncology (ASTRO) recently performed a longitudinal survey, which indicated that patient access to radiotherapy was preserved during the pandemic, and most institutions did not defer or postpone the treatment in early 2021. In addition, telemedicine was commonly used in metropolitan areas [ 9 ]. In Japan, some institutions experienced a decrease in the number of patients receiving radiotherapy, and the number of patients was limited in the early stages of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the pre-COVID-19 period with the COVID-19 period, the number of new colorectal cancer diagnoses decreased significantly by 32.9% for Stage 0, 34% for Stage I and 35.3% for Stage II, while it increased significantly by 68.4% for Stage III [ 11 ]. Furthermore, the ESTRO [ 8 ] and ASTRO [ 9 ] surveys outlined the problem of high rates of advanced-stage cancers during the pandemic, which might become an issue in oncology in the future. The workload on radiotherapy departments may increase with an increase in the number of patients with advanced-stage cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the nine reports; six are multi‐institutional studies, two are single‐institution studies, and one is an expert review from European Society of Paediatric Oncology (SIOPE) Radiation Oncology Working Group 8–16 . Four studies consisted of surveys delivered to pediatric oncology institutions or providers, and three studies consisted of patient registry data 8,10,12–16 . Two studies consisted of data from around the world through the St. Jude Global Alliance and International Society for Pediatric Oncology networks 15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…Two studies consisted of data from around the world through the St. Jude Global Alliance and International Society for Pediatric Oncology networks 15,16 . Two reports consisted of data from Europe, two from the United States, one from Latin America, one from India, and one from the Middle East, North Africa, and West Asia 8–14 (Table 1).…”
Section: Methodsmentioning
confidence: 99%